A proposed algorithm for early autism screening in Polish primary care settings – a pilot study - Patryk Domarecki; Katarzyna Plata-Nazar; Wojciech Nazar (BMC Primary Care)
Abstract Background The rising rate of autism spectrum disorder (ASD) prevalence worldwide demands new screening algorithms to make the process of diagnosis more effective. General practitioners and pediatricians are well-positioned to screen all children aged 16 to 30 months during regular check-ups. In the research, the original algorithm for early autism screening in Polish primary care settings was proposed and tested. Methods Based on the literature review, the original algorithm of early autism screening employing observational tool was developed and tested. Personal data and M-CHAT-R/F were collected online. In the second phase, chosen patients participated in the Screening Tool for Autism in Toddlers and Young Children (STAT). Children who scored positive were referred for the comprehensive ASD evaluation. Normal distribution was analyzed with the use of the Shapiro–Wilk test. Chosen variables were compared using the U-Mann Whitney (nonparametric data) or Student’s t-test (parametric data). The Spearman’s rank correlation coefficient was calculated to analyze the strength of association between selected continuous variables. The threshold of the two-sided statistical significance was set at p < 0.05. Results Of 187 parents invited to the project, 159 filled the form in the first phase. According to the protocol, 29 children were chosen for the second stage. 10 children scored positive in the STAT session and were referred for comprehensive evaluation. 5 children out of the seven who attended the evaluation received a final diagnosis of ASD. Parental concerns were found the strongest predictor of M-CHAT-R/F results. Fear of having a child with ASD diagnosis was the most common reason for withdrawal from further steps of the protocol. Conclusions The proposed algorithm for early developmental screening in the Polish primary care settings is a promising pathway with the potential to be implemented in clinical practice. It contributes to the early detection of developmental difficulties and therefore results in positive therapeutic outcomes. Further research is needed.